Pork and Chicken Meals Similarly Impact on Cognitive Function and Strength in Community-Living Older Adults: A Pilot Study. Issue 2 (2nd April 2016) - Charlton, Karen; Walton, Karen; Batterham, Marijka; Brock, Erin; Langford, Kelly; McMahon, Anne; Roodenrys, Steven; Koh, Freda; Host, Alison; Crowe, Ruth; Thornhill, Kayla
ABSTRACT: A pilot quasi-experimental study investigated whether provision of pork, a rich source of thiamin, as the main protein source in meals four times/week for 12 weeks resulted in improved muscle mass, body strength, and cognitive function in community-living older adults compared to similar meals containing chicken. Retirement villages were randomized to receive pre-prepared frozen meals containing either pork or chicken. Dietary intake was assessed by three-day food records and cognitive domains assessed using validated tests. Hand grip strength was measured and lower extremity performance assessed by the sit-to-stand test, get-up-and-go test and six-minute walk test. Forty-eight volunteers participated (78.2 ± 6.2 y). In linear mixed models, controlling for baseline physical activity and dietary protein and energy intake, no differences were found between pork (n = 19) and chicken (n = 12) groups. The chicken group had improved Rey Auditory Verbal Learning test scores (verbal learning and memory) at six weeks (p < 0.001). Provision of four pork meals a week did not result in improvements in cognitive function, nor measures of strength or physical function, compared to those receiving chicken meals in healthy older adults. This suggests that merely changing the type of dietary protein provided by meat does not impact physical or cognitive function.